Copyright Challenges in Today's Technologically Advanced Cyberspace - Eva Ndenzako (Uganda Christian University, 2024)
Copyright law is a branch of intellectual property law that provides a legal foundation for the innumerable transactions by which authors, artists and composers of qualifying works and neighboring rights are aid for their intellectual creativity. This protection extends to a number of works but in Uganda the scope of copyright protection is enshrined in Section 5 of the Copyright and Neighboring Rights Act to include literary works, dramatic works, musical works, artistic works and derivative works. This research study focuses on the need for copyright laws to change in response to technological advancements because they are not sufficient and comprehensive enough to regulate the enforcement of copyright protection given the speed of technological developments in the cyber space today.